Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Pegawai Negeri Sipil Dengan Motivasi Kerja Sebagai Moderasi (Studi Empiris Pada BKPSDM Kabupaten Pasaman) - Sherly Destri Alda; Heliyani Heliyani (Jurnal Mirai Management, 2023)
The existence of the Pasaman District Civil Service and Human Resources Development Agency (BKPSDM) as a government institution is mandatory to carry out tasks in organizing the organization and developing the competencies of human resources and civil servants. This agency is authorized and responsible for serving the interests of the community and civil servants who require high-performance employees. In order to achieve the organization's goals, every organization needs resources to accomplish them, including natural resources, financial resources, knowledge and technology resources, and human resources. The purpose of this research is to determine the influence of competence and work discipline on performance, with work motivation as a moderator. The research method used a quantitative approach with the Partial Least Square approach using the Structural Equation Modeling equation model. Data collection techniques involved questionnaires and observations. The respondents of this study were 45 civil servants working in the Pasaman District Civil Service and Human Resources Development Agency. The sampling method used total sampling. Hypothesis testing was conducted using the SmartPLS program. The results of this study indicate that, partially, competence and work discipline have a positive and significant effect on performance. However, work motivation does not have a positive and significant effect on performance. Additionally, work motivation as a moderator does not have a positive and significant influence on the relationship between competence, work discipline, and the performance of civil servants at the Pasaman District Civil Service and Human Resources Development Agency.